2016
DOI: 10.4103/0972-5229.195702
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a prognostic score for mortality in elderly patients admitted to Intensive Care Unit

Abstract: Context:The performance of a prognostic score must be evaluated prior to being used. The aim of the present study was to evaluate the predictive ability of hospital mortality of Simplified Acute Physiology Score 3 (SAPS 3) score in elderly patients admitted to Intensive Care Units (ICUs).Aims:The aim of the present study was to evaluate the SAPS 3 score predictive ability of hospital mortality in elderly patients admitted to ICU.Settings and Design:This study was conducted as a prospective cohort, in two mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the general population, SAPS3 demonstrated good accuracy in prediction of ICU mortality and it performed fairly in the very elderly subset of our critically ill cohort. Prior studies have demonstrated similar reductions in the accuracy of SAPS3 and other severity scores in elderly patients admitted to the ICU [ 9 ]. Notably, the novel ACIS tool outperformed the SAPS3 in our 80 years or older population and most other age strata.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the general population, SAPS3 demonstrated good accuracy in prediction of ICU mortality and it performed fairly in the very elderly subset of our critically ill cohort. Prior studies have demonstrated similar reductions in the accuracy of SAPS3 and other severity scores in elderly patients admitted to the ICU [ 9 ]. Notably, the novel ACIS tool outperformed the SAPS3 in our 80 years or older population and most other age strata.…”
Section: Discussionmentioning
confidence: 86%
“…Scoring systems, such as the Simplified Acute Physiology Score, have been validated and long used in ICUs around the world to assess the severity of illness. However, these scores did not include an aging population at time of validation, suggesting that their discriminatory capacity may diminish in the coming years with a complex very elderly population [7][8][9]. This study aims to determine the accuracy of the Simplified Acute Physiology Score (SAPS3) in patients admitted to a general ICU and identify variables associated with mortality to develop an alternative age calibrated scoring system.…”
Section: Introductionmentioning
confidence: 99%